New ways of seeing Picasso, Braque and the cubist revolution ([Chicago, Ill.] Home Vision [distributor], 1898)
Documents the extraordinary exhibition mounted by the Museum of Modern Art and presents a rare and provocative view of cubism and the inspired collaboration of Picasso and Braque.
VHS format.
Executive producers : Stephanie French, Philip Morris Company Inc., and Minkoff / Clayman Productions.
Keywords: Picasso, Pablo, 1881-1973.; Cubism; Art -- France -- 20th century